Brain Box Learning Centre / Syarifah Aiman Mardhiah Wafa Syed Abdul Hamid ... [et al.] - Syed Abdul Hamid, Syarifah Aiman Mardhiah Wafa; Rahmat, Fatimah; Ahmad Zahir, Zetty Nur Aida; Mohd Yusoff, Maisarah Meor; Abdul Mutalip, Umi Syahidah (2018)
This business is based on partnership where it of five (5) members which hold important position in the company such as General Manager , Adminstration , Financial Executive and Facilitator. The business own capital is RM40,000.00 and the rest RM120,000.00. Brain Box Learning Centre is a platform that can help to increase the education performance, increase potential to get more excellent result and success in academics for all of the existing students.The tuition class will not only gives basic education and guidance to the group of students in the tuition, but it also enable the student to build more confidence in facing examinations. Brain Box Learning Centre marketing strategy is to emphasize the product , place, price and promotion. We offer service with fee that is reasonable to primary school children and secondary to achieve excellence in education. Brain Box Learning Centre will prove system and expertise that be, beside administrative management, promotion, tutor management and schedule good leaners make business being perfomed increasingly grow. This will give more advantages for us to make our product or service more profitable and stable in the long run.